2019
DOI: 10.3389/fmicb.2019.01002
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of New Endemic Clusters of Human T-Cell Leukemia Virus (HTLV) Infection in Bahia, Brazil

Abstract: Background Salvador, Bahia (northeastern Brazil), has been identified as the epicenter of Human T-cell leukemia virus Human T-cell leukemia virus (HTLV) type 1 infection in the country. This study aims to estimate the rate of HTLV infection and the geographical distribution of this virus in this state. Methods All HTLV tests (chemiluminescence/ELISA assays/Western Blotting) performed in the Central Laboratory of Public Health of Bahia (LACEN) from 2004 to 2013 were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 36 publications
0
23
0
4
Order By: Relevance
“…The history of HTLV is a fascinating one regarding its possible origin in the African continent and its spread in different directions according to human migration routes [4], and the ARB is of paramount importance because of the presence of a specific strain of the virus that originated during human migration into the area and its further dissemination to other geographical areas in the country and abroad [36,51,[91][92][93][94][95][96][97].…”
Section: The Amazon Region Of Brazilmentioning
confidence: 99%
“…The history of HTLV is a fascinating one regarding its possible origin in the African continent and its spread in different directions according to human migration routes [4], and the ARB is of paramount importance because of the presence of a specific strain of the virus that originated during human migration into the area and its further dissemination to other geographical areas in the country and abroad [36,51,[91][92][93][94][95][96][97].…”
Section: The Amazon Region Of Brazilmentioning
confidence: 99%
“…In the Ilhéus-Itabuna and Porto Seguro microregions, both located in the southernmost region of the state, tourism and commercial activities are essential to the local economy. Recently, these two microregions were highlighted as significant foci of HTLV-1 infection [9].…”
Section: Plos Onementioning
confidence: 99%
“…In Brazil, the prevalence of HTLV-1 varies according to geographic location, with the North and Northeast regions being the most affected [ 8 ]. Recently, it was reported that HTLV-1 is widespread throughout the state of Bahia, with at least 130,000 individuals infected with this virus [ 9 ]. While HCV infection affects around 2.5% of the world's population (177.5 million adults), a population-based study in Brazil focusing on all 26 state capitals and the Federal District found an overall HCV seroprevalence of 1.38% [ 10 ]; in Salvador, 1.5% of the general population is estimated to be infected with HCV [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…2019 ), although it is possible to locate geographical areas with pockets of low and very high prevalence and incidence ( Jensen et al. 2019 ; Pereira et al. 2019 ; Pham et al.…”
Section: Introductionmentioning
confidence: 99%